Teori Kontrak Sosial (Studi Komparasi Teori Politik Menurut Imam Al-Mawardi, Thomas Hobbes Dan John Lock) - Mohamad Nur Wahyudi (Indonesia, 2022)
Scientists have agreed to mark the times of revival in Islamic civilization, namely in the Middle Ages or the Classical century, while this revival in Islamic civilization can be seen, one of which is the development of science ranging from the fields of economics, politics, and in the field of medicine. In the field of Islamic politics, for example, it has received special attention from a philosopher as well as a scholar, namely Imam al-Mawardi, in the field of Islamic politics, the contribution of Imam al-Mawardi can be seen in his book, al-Ahkam al-Sulthaniyah. While broadly speaking, this study aims to further read Imam al-Mawardi's theory of social contract by comparing it with several Western philosophers who also have social contract theory such as Thommas Hobbes, thus this research can also be called a comparative study of the thoughts of figures and theories. used in this study also uses political theories of social contract from several philosophers.